Health of men, women, and children in post-trafficking services in Cambodia, Thailand, and Vietnam: an observational cross-sectional study. Issue 3 (March 2015) - Kiss, Ligia; Pocock, Nicola S; Naisanguansri, Varaporn; Suos, Soksreymom; Dickson, Brett; Thuy, Doan; Koehler, Jobst; Sirisup, Kittiphan; Pongrungsee, Nisakorn; Nguyen, Van Anh; Borland, Rosilyne; Dhavan, Poonam; et al.
Summary: Background: Trafficking is a crime of global proportions involving extreme forms of exploitation and abuse. Yet little research has been done of the health risks and morbidity patterns for men, women, and children trafficked for various forms of forced labour. Methods: We carried out face-to-face interviews with a consecutive sample of individuals entering 15 post-trafficking services in Cambodia, Thailand, and Vietnam. We asked participants about living and working conditions, experience of violence, and health outcomes. We measured symptoms of anxiety and depression with the Hopkins Symptoms Checklist and post-traumatic stress disorder with the Harvard Trauma Questionnaire, and used adjusted logistic regression models to estimate the effect of trafficking on these mental health outcomes, controlling for age, sector of exploitation, and time in trafficking. Findings: We interviewed 1102 people, of whom 1015 reached work destinations. Participants worked in various sectors including sex work (329 [32%]), fishing (275 [27%]), and factories (136 [13%]). 481 (48%) of 1015 experienced physical violence, sexual violence, or both, with 198 (35%) of 566 women and girls reporting sexual violence. 478 (47%) of 1015 participants were threatened and 198 (20%) were locked in a room. 685 (70%) of 985 who had data available worked 7 days per week and 296 (30%) of 989 worked at least 11 hours per day. 222 (22%) of 983 had a serious injury at work. 61·2% (95% CI 58·2–64·2) of participants reported symptom of depression, 42·8% (39·8–45·9) reported symptoms of anxiety, and 38·9% (36·0–42·0) reported symptoms of post-traumatic stress disorder. 5·2% (4·0–6·8) had attempted suicide in the past month. Participants who experienced extremely excessive overtime at work, restricted freedom, bad living conditions, threats, or severe violence were more likely to report symptoms of depression, anxiety, and post-traumatic stress disorder. Interpretation: This is the first health study of a large and diverse sample of men, women, and child survivors of trafficking for various forms of exploitation. Violence and unsafe working conditions were common and psychological morbidity was associated with severity of abuse. Survivors of trafficking need access to health care, especially mental health care. Funding: Funding Anesvad Foundation and IOM Development Fund.